Case Study: Aphonia in Psychosis: Bridging ENT and Psychiatry - Akansha Tewari; Andrea Pathak; Ashish Pathak; Abhinav Tewari (BJPsych Open)
Aims: Aphonia, defined as partial or complete loss of voice, can have multifactorial origin, ranging from organic to functional aetiology. This paper aims to describe an unusual presentation of aphonia on the background of psychotic symptoms and catatonia.